Effect Alumina of Al-Al2O3 Composite and Squeeze Casting Pressure on Tensile Strength and Microstructure - Sri Mulyo Bondan Respati; Saiful Amin; Helmy Purwanto (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Squeeze casting or often also called liquid metal forging is a process in which molten metal is inserted in the mold and pressed. This study aims to determine the alumina effect and the pressure effect of squeeze casting against tensile strength and microstructure of AL-Al2O3 composite. In this study, used a variation of pressure of 100 MPa, 120 MPa, and 140 MPa and weight percent alumina of 5%wt, 10%wt, and 15%wt. The results of this study showed the highest tensile tests on specimens with a mixture of 10%wt alumina and 140 Mpa pressure with an average yield of 215 MPa, as for his dendrite spacing was 17.62 mm. It is revealed that the addition of an alumina to the Al-Al2O3 composite will raise the strength of 10% by weight of alumina. Keywords: squeeze casting, Aluminum, Alumina.